The zircon ‘matrix effect’: evidence for an ablation rate control on the accuracy of U–Pb age determinations by LA-ICP-MS - Marillo-Sialer, E.; Woodhead, J.; Hergt, J.; Greig, A.; Guillong, M.; Gleadow, A.; Evans, Noreen; Paton, C. (Royal Society of Chemistry, 2014)
Many studies now acknowledge the occurrence of systematic discrepancies between U–Pb ages determined in zircons in situ by LA-ICP-MS and the benchmark analytical method ID-TIMS. In this study, we present detailed investigations into the ablation characteristics of zircons that suggest an underlying mechanism responsible for these age biases relative to ID-TIMS. Confocal laser scanning microscopy of laser ablation pits reveals that there are small but significant differences in the amount of material removed by the laser between different zircons. Based on numerous pit depth and LA-ICP-MS 206Pb/238U ratio measurements of a suite of natural zircon reference materials and samples, we demonstrate that a systematic age bias is strongly correlated with the offset in ablation rates between the primary reference material and sample zircons. We offer further insights concerning the effects of thermal annealing on the ablation behaviour of zircons and demonstrate that, although there is a change in laser ablation rates for annealed zircons, the variations between different zircons are not eliminated. Finally, we show that slight variations in laser focus also influence the ablation behaviour of zircons and may further degrade the accuracy of U–Pb age determinations.